ANALISIS EFEKTIFITAS KINERJA DIVISI GENERAL AFFAIR (STUDI KASUS PADA POLITEKNIK LP3I JAKARTA KAMPUS DEPOK) - Farizal Marzuki (POLITEKNIK LP3I JAKARTA, 2025)
This study was conducted to determine the analysis of the effectiveness of the General Affair Division's performance at the LP3I Jakarta Polytechnic, Depok Campus. The purpose of this study was to determine the Analysis of the Effectiveness of the General Affair Division's Performance at the LP3I Jakarta Polytechnic, Depok Campus. Data collection techniques through observation, namely directly observing the object being studied. Based on the results of the discussion, it shows that employee performance assessments at the LP3I Jakarta Polytechnic, Depok Campus assess performance based on Employee Attitude, taking the initiative in working, and also achievements/rewards as well as in terms of discipline and also the quality of employee work, not forgetting the HRD assessment. The obstacles that occur in the performance appraisal process are still not optimal, then the appraisal process that should be carried out routinely every 3 months, which only occurs when the employee's contract expires, and the lack of training and development for employees. Then the solution carried out by the HRD department is to have an employee track record in both hard and softcopy forms, conduct staff assessments according to the company's schedule and procedures, and create an assessment planning timeline, then carry out training based on basic skills in each field or training submitted by each field.